Youth Movement in Indonesia: Omnibus Law Demonstration - Anridho, Claudia (Studi Budaya Nusantara, 2024)
Youth movement is crucial in Indonesia because since the beginning of Indonesia’s independence, the young generation has been one of the main actors. This article aims to examine the youth movement that occurred in 2020. University student groups held demonstrations against the controversial omnibus law in almost every major city in Indonesia. The protests against the job creation omnibus law, which originated as a bill, occurred across regions in Indonesia on February 12 and October 20, 2020. This youth movement to reject the omnibus law is proof that despite many societal groups rejecting the bill, the government continues with its decision due to differences in perspective. Yet, this action remains a right of young people to express their aspirations regarding the political situation in Indonesia. Differences in opinion may incite youth to demonstrate against government bills and judgments